Inflammation, Glutamate, and Cognition in Bipolar Disorder Type II: A Proof of Concept Study - King, Sinead; Jelen, Luke A.; Horne, Charlotte M.; Cleare, Anthony; Pariante, Carmine M.; Young, Allan H.; Stone, James M. (Frontiers in Psychiatry, 2019)
BACKGROUND: Two current theories regarding the neuroscientific bases of mood disorders involve alterations in glutamatergic neurotransmission and excessive activation of inflammatory pathways. We hypothesized that glutamate (Glu) levels and peripheral inflammatory markers would be associated with cognitive function, in patients with Bipolar Disorder Type II (BP-II), and that such factors would be associated with psychological treatment outcomes. AIMS: The primary aim of this study was to explore the relationship between the neurotransmitter Glu, cytokines (CRP, IL_6 and TNFa) and neuropsychological and related functioning. The secondary aim was to assess cognitive functioning as a predictor of poor response to psychological therapy. METHODS: Proton magnetic resonance spectroscopy data were acquired from the anterior cingulate cortex of 15 participants with BP-II, and 13 healthy controls in a 3T magnetic resonance imaging scanner. The Digit Symbol Task (DST) for processing speed, TMT-B for executive function and Rey Auditory Verbal Learning Test (RAVLT) were administered to assess cognitive domains. RESULTS: There was no significant difference in anterior cingulate Glu, or inflammatory markers between groups. Furthermore, we found no significant difference between groups in any cognitive tests. Scores on the DST were found to be significantly associated with poor response to psychological therapy. CONCLUSIONS: This study may highlight an association between neuropsychological dysfunction and treatment outcome in euthymic patients with BP-II. We did not find any association between peripheral inflammatory markers and brain Glu levels. This may have been in part due to the small sample size.